The Exalted Islamic Ethics towards Conquest of Fintech - Osman, Adibah Alawiah; Abdullah, Azwan; Ab Rahman, Siti Maziah; Safian, Sharul Shahida Shakrein; Ibrahim, Nor Zawani Mamat; Mohd Masdek, Nik Rozila Nik; Shaharuddin, Norhasimah (Information Management and Business Review, 2023)
Ethics is the conduct that is transmitted from the understanding of norms into a person’s attributes. The essential of exalted ethics, especially regarding Shariah compliance has a strong basis of knowledge as it depends on the Quran and Sunnah. The delivery of knowledge for Islamic Finance while possessing Islamic Ethics is vital for weighing Shariah compliance in a holistic manner for the conquest of Finance Technology (FINTECH). It is important to note that numerous prior researchers have done most of the research that regards Islamic Ethics. The secondary data of the Maqasid al-Syariah variables from Islamic financial institutions of specified sectors is to be taken for assessment. The partial least squares structural equation modelling (PLS-SEM) method was the main statistical technique to be employed in this study. This study fits its real purpose by offering an accurately precise mode of Islamic Ethics in influencing the accomplishment of Islamic Fintech. In particular, the study of Islamic Ethics influences the direction of the religious aims as well as the accurate application of Islamic Fintech.